STRATEGI PENGEMBANGAN KAMPUNG NELAYAN PASAR BENGKULU SEBAGAI KAWASAN WISATA KOTA BENGKULU - Meiffa Herfianti; Yesi Indian Ariska (Unib Press Universitas Bengkulu, 2018)
The pattern of development in the city of Bengkulu is directed at building tourism and its development. This is because most of the city of Bengkulu is in the coastal region of the Indonesian Ocean. The potential of tourist areas in the city of Bengkulu is very large, especially for the development of tourism based on sea and fisheries. The Bengkulu City Government has established coastal area development programs, one of which is in Bengkulu Market Fisheries Village. Facilities and infrastructure supporting coastal tourism have been sought by the Bengkulu City government such as the construction of tourist area entrances, shelters, parking lots and other supporting facilities. Other support is to mobilize the community to sell Bengkulu special culinary and other sea culinary, so that the development of fisherman villages as tourist areas can be achieved.